Variants of Monteggia type injury: Case reports - Kamudin, NAF; M Firdouse, .; MB BcH, BAO (2015)
Background: Monteggia fracture-dislocation is rare in children. Various reports attest to its rarity, while recording the many variant of this injury. It is, therefore, easy to miss the diagnosis in the absence of proper clinical examination and radiographs. Case Report : This report highlights two rare variants of Monteggia fracture-dislocation seen in children. The first case was a 12-year old girl alleged to have fallen from a 15- feet tall tree and sustaining a combined type III Monteggia injury with ipsilateral Type II Salter-Harris injury of distal end radius with a metaphyseal fracture of the distal third of the ulna. The second case was a 13-year old who had sustained a closed fracture of atypical Type I Monteggia hybrid lesion, in a road traffic accident. Conclusion: This report highlights the rare variants of Monteggia fracture dislocation which could have been missed without proper clinical examinations and radiographs.